Medicinal plants with cholesterol-lowering effect marketed in the Buenos Aires-La Plata conurbation, Argentina : An Urban Ethnobotany study - Hurrell, Julio Alberto (2015)
Fil: Hurrell, Julio Alberto. Laboratorio de Etnobotánica y Botánica Aplicada (LEBA). Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina